Discretion and Decentralization: Public Administrators Dilemmas in Bureaucracy Innovation Initiatives - Lesmana Rian Andhika (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
Policy discretion shall not be construed as a free authority by the public administrator. The positive side discretion is answered to an urgent need, the ambiguity caused the existing policy. The focus this researched would like to explore further the public administrator dilemmas perform some correlation between policy discretion and decentralization, discretion and initiation of bureaucracy innovation. The research method applied is qualitative, descriptive analysis is adopted based on secondary data and information sources. Triangulation is used to draw conclusions carefully from a variety of data sources. The research concludes the initiation of bureaucracy innovation is the urgent needs at this time, and discretion one of the tools that can be used as a policy outside the formal policy not set explicitly on the different the element related with innovation. The unique thing is not all public administrators like and can do discretion, there is a logical consideration that must be met to assess and translate discretion, capability and sufficient knowledge is some logical considerations it is. Bias interpretation will cause negative effects like opening a chance doing the corruption, collusion, nepotism and the occurrence of criminalization policy procedures.